Statistika Kependudukan Untuk Rencana Kebijakan Kependudukan Daerah - Achmad Isya Alfassa (Pusat Kajian Demografi, Etnografi dan Transformasi Sosial, 2022)
Population statistics is a science that studies two branches of science, namely statistics and population science. These two branches of science are integrated in population statistics to help solve population problems through statistical analysis and are used as recommendations in making regional population policy decisions. This study uses secondary data from the publications of Indragiri Hilir Regency in numbers and aims to provide an understanding of population statistics in terms of terminology and philosophy of science and can be used in the preparation of regional population policy plans. The results of this study explain that the terminology of population statistics consists of fertility, mortality, and migration, while the philosophy of population statistics consists of axiology, ontology, and epistemology. In the preparation of the regional population policy plan with the demographic concept, there are 5 groups of population policy plans, including the Fertility Group, School Productive Age Group, Work Productive Age Group, Retirement Age Group, and Elderly Age Group. Key words: Statistics Population, Indragiri Hilir Regency, Statistics, Population, Demography, Population Policy.